HUMAN RIGHTS AND INDONESIAN LEGAL PROTECTION OF TRADITIONAL CULTURAL EXPRESSIONS: A Comparative Study in Kenya and South Africa - Widyanti, Yenny Eta (Jurisdictie: Jurnal Hukum dan Syariah, 2023)
Legal protection of traditional cultural expressions in Indonesia is paramount to human rights. Indonesia is home to its richness of cultures and tribes, offering economic, social, and cultural values. However, this potential will remain insignificant without proper regulatory provisions in the domains of intellectual property or human rights. Departing from this issue, this research seeks to profoundly analyze the interface between traditional cultural expressions and human rights from the perspectives of either national law or international convention, and this analysis involves the comparison between Kenya and South Africa that appropriately govern legal protection of human rights in traditional cultural expressions. This research aims to elaborate on the interface between human rights and the protection of traditional cultural expressions within the purviews of national law and an international convention. With a legal research method and statutory, conceptual, and comparative approaches, this research finds that there is a close correlation between traditional cultural expressions and human rights, as referred to in international laws in Indonesia, Kenya, and South Africa, and the international convention. This research is expected to serve as a reference for Indonesian national law, in which adopting the best practices in Kenya and South Africa can be taken into account. Perlindungan hukum Ekspresi Budaya Tradisional Indonesia adalah pending untuk diwujudkan sebagai bagian dari hak asasi manusia. Fakta Indonesia sebagai negara yang kaya dengan keanekaragaman budaya dan suku bangsa menjadi potensi luar biasa nilai ekonomi, sosial dan budaya. Potensi luar biasa tersebut tidak dapat diwujudkan tanpa diikuti pengaturan hukum yang memadai baik di bidang hak kekayaan intelektual maupun hak asasi manusia. Atas dasar hal tersebut, menjadi penting untuk menganalisis keterkaitan ekspresi budaya tradisional dengan hak asasi manusia dalam hukum nasional, konvensi internasional, dan perbandingan di negara-negara Afrika, yaitu Kenya dan Afrika Selatan yang telah mengatur dengan baik perlindungan hukum atas hak asasi ekspresi budaya tradisional. Penelitian ini bertujuan untuk memaparkan interface hak asasi manusia dengan perlindungan ekspresi budaya tradisional baik dalam hukum nasional maupun konvensi internasional. Jenis penelitian hukum dengan pendekatan perundangan, konseptual, dan perbandingan maka ditemukan bahwa terdapat hubungan yang erat antara ekspresi budaya tradisional dengan hak asasi manusia sebagaimana terdapat dalam pengaturan di dalam hukum nasional Indonesia, Kenya, Afrika Selatan, dan konvensi internasional. Penelitian diharapkan dapat menjadi rujukan dalam hukum nasional Indonesia dengan mengadopsi praktik terbaik di Kenya dan Afrika Selatan.